Construction of Dopamine Hydrochloride Liquid Selective Electrodes - A. Hammza, Rana (Al-Nahrain Journal of Science, 2024)
Three liquid selective electrodes were synthesized based on particle pair to selective dopamine chloride. The construction electrodes consist of phosphomolybdic acid (dopamine), di-n-butyl phosphate, Di-n-butyl phthalate, and di-octylphenylphosphonate as plasticizers materials. The construction of preparing probes was examined potentially with successes   Nernstain response around 52.50 and 50. 50 mV/decade for electrodes on both DBPH and DOPH were as plasticizers, respectively. The most direct ranges concentrations of dopamine in drug form were found to be around 2.5×10-5-1.0×10-2 for DBPH and 4.30×10-5 -1.0×10-1 M for DOPH. The detection limits were reached to 2.31×10-6 in DBPH and 5. 63×10-6 M in DOPH electrode type. While third electrode relied on di-n-butyl phosphate (DPH), a non-Nernstain equivalent of around 19.10 mV/decade with a range of concentration about 2.2×10-5 -1.0×10-1 with a detection limit equivalent to 6.35×10-6. The pH values in the experimental application were asses to obtain the best determination of dopamine concentration at 10-3M. The optimisation of both electrodes DBPH and DOPH achieved good agreements to lifetime, selectivity, potentiometric techniques and accuracy of measurements. At the same time the standard expansion, various standard expansions and potentiometric titration result in an immediate strategy for the assurance of dopamine in drug form.